More online, less lonely? The buffering role of online communication on the relationship between health and loneliness among late middle-aged and older adults - Daria Turavinina; Yot Amornkitvikai (Social Sciences and Humanities Open)
As technology continues to shape our social interactions, understanding its impact on late middle-aged and older adults' wellbeing is crucial. This study, therefore, examines the association between online communication and loneliness among a sample of 14,727 late middle-aged and older adults, with a particular emphasis on individuals with poorer health. Controlling the total frequency of social interactions, our findings suggest that increased online communication may not always lead to decreased loneliness. In fact, excessive reliance on online connections is likely to greatly contribute to feelings of isolation, lack of companionship, and being left out. This aligns with the displacement hypothesis, which suggests that digital interactions are unlikely to fully substitute for in-person social connections. Nonetheless, for late middle-aged and older persons with health constraints, internet communication may be an effective tool for preserving social relationships. This study indicates that late middle-aged people have the highest levels of loneliness. It can assist in bridging physical barriers and create possibilities for social engagement that might otherwise be unavailable. A balanced strategy is advocated for mitigating the negative effects of online communication while maximizing its advantages. A combination of in-person and online social activities is crucial for promoting the well-being of late middle-aged and older adults.